2013
DOI: 10.1002/pmic.201300082
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ubiquitinated proteins by proteomics reveals the role of the ubiquitin proteasome system in the regulation of Grp75 and Grp78 chaperone proteins during intestinal inflammation

Abstract: The ubiquitin proteasome system (UPS) is the major pathway of intracellular protein degradation and may be involved in the pathophysiology of inflammatory bowel diseases or irritable bowel syndrome. UPS specifically degrades proteins tagged with an ubiquitin chain. We aimed to identify polyubiquitinated proteins during inflammatory response in intestinal epithelial HCT-8 cells by a proteomic approach. HCT-8 cells were incubated with interleukin 1β, tumor necrosis factor-α, and interferon-γ for 2 h. Total cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…The mechanism by which DMC decreases GRP78 protein expression was not investigated in our study. GRP78 is regulated by protein degradation through the proteasome but also cathepsins (Shi et al, 2009;Bertrand et al, 2013). In our study, we could not revert Mcl-1 downregulation and DMC-induced apoptosis with the proteasome inhibitor MG132, thus suggesting a proteasome-independent effect.…”
Section: Dmc Induces Apoptosis and Cell Cycle Alterations In Leukemiasupporting
confidence: 46%
“…The mechanism by which DMC decreases GRP78 protein expression was not investigated in our study. GRP78 is regulated by protein degradation through the proteasome but also cathepsins (Shi et al, 2009;Bertrand et al, 2013). In our study, we could not revert Mcl-1 downregulation and DMC-induced apoptosis with the proteasome inhibitor MG132, thus suggesting a proteasome-independent effect.…”
Section: Dmc Induces Apoptosis and Cell Cycle Alterations In Leukemiasupporting
confidence: 46%
“…Similarly to previous studies[13-15,17-20], we observed colon inflammation demonstrated by stiffened colon, histological inflammatory score or increased inflammatory markers. We also noted SPECT signs of inflammation such as an increased maximal thickness of colon.…”
Section: Discussionsupporting
confidence: 88%
“…Colitis was induced at day 0 by administration of TNBS (Sigma-Aldrich, Saint-Quentin Fallavier, France) as previously described[13,15,16]. The rats were then briefly anesthetized with an intraperitoneal injection of ketamine and chlorpromazine following 24-h food deprivation.…”
Section: Methodsmentioning
confidence: 99%
“…reported single nucleotide polymorphisms in several genes involved in the UPS in CD patients and that adherent‐invasive Escherichia coli modified NF‐κB activation through the regulation of UPS turnover in intestinal epithelial cells . In a previous study, we showed that UPS also regulated the expression of other proteins, that is, HSPs, during intestinal inflammatory response both in vitro and in vivo by using a proteomic approach .…”
Section: Introductionmentioning
confidence: 87%
“…After transfer, membranes were blocked with 5% w/v BSA (fraction V, Eurobio) in (TBS (10 mM Tris, pH 8; 150 mM NaCl) plus 0.05% v/v Tween 20 = TBS‐T). After washes with TBS‐T, membranes were incubated overnight at 4°C with rabbit polyclonal anti‐ubiquitin (1:500, SantaCruz Biotechnology, Le Perray en Yvelines, France), then washed again and incubated with swine anti‐rabbit IgG HRP conjugated (1:5000, Dako, Trappes, France) as previously described . Immunocomplexes were revealed by using the ECL detection system (GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%